Impact of Stakeholder Psychological Empowerment on Project Success - Chandra, Herry Pintardi; Indarto; Wiguna, I Putu Artama; Kaming, Peter F. (IPTEK The Journal for Technology and Science, 2025)
The relationship between psychological empowerment of stakeholders and project success is an important thing that must be known by project manager. This research developed and tested the model to predict how well the impact of stakeholder psychological empowerment on project success. Stakeholder psychological empowerment was defined to have five indicator variables covering intrinsic motivation, opportunity to perform, ability to perform, task behaviors, and contextual behaviors. Meanwhile, project success can be measured by cost performance, time performance, quality performance, profitability, and customer satisfaction. In this study, it was hypothesized that stakeholder psychological empowerment influenced project success. Based on the data obtained from a questionnaire survey carried out to 204 respondents, structural equation modeling (SEM) was used for predicting the performance of project success. It was found that stakeholder psychological empowerment influenced project success, especially on the ability to perform of stakeholders.